2018
DOI: 10.1007/s10620-018-5005-8
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment Efficacy of Sofosbuvir/Ombitasvir/Paritaprevir/Ritonavir + Ribavirin for Hepatitis C Virus Genotype 4 Patients

Abstract: The recent multi-targeted regimen of SOF plus OBV/PTV/r + RBV was well tolerated and achieved excellent SVR rates among retreatment-experienced Egyptian patients with prior DAA treatments failure, thus providing an alternative regimen for the retreatment of difficult-to-cure HCV GT4 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…The current study showed no significant difference in SVR12 rates achieved by noncirrhotic patients (96.8%) and that achieved by cirrhotic patients (100%), which was in accordance with other studies by Abdel‐Moneim and colleagues 25,27 . In patients who used SOF/DAC/SMV/RBV, the SVR12 rates were 91% and 99% in cirrhotic and noncirrhotic patients, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study showed no significant difference in SVR12 rates achieved by noncirrhotic patients (96.8%) and that achieved by cirrhotic patients (100%), which was in accordance with other studies by Abdel‐Moneim and colleagues 25,27 . In patients who used SOF/DAC/SMV/RBV, the SVR12 rates were 91% and 99% in cirrhotic and noncirrhotic patients, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In SOF/OBV/PTV/r + RBV group, SVR12 rates were 98.8%. Similar results were published by Abdel‐Moneim et al 27 who retreated 113 Egyptian CHC patients who failed to respond to prior DAA therapy, by SOF/OBV/PTV/r/RBV for 12 weeks. SVR12 was achieved in 109 patients (97%).…”
Section: Discussionsupporting
confidence: 86%
“…The regimen is effective with non-approved triple combinations such as sofosbuvir, daclatasvir, simeprevir plus ribavirin or sofosbuvir with grazoprevir and elbasvir plus ribavirin. These regimens may be useful in regions in which triple therapy is not available 8991 . Moreover, preliminary data from a phase 3b study evaluating glecaprevir and pibrentasvir treatment of patients with HCV genotype 1 infection failed by an NS5A inhibitor and sofosbuvir (with or without ribavirin) indicated that 95% of patients maintained an SVR for 4 weeks after treatment.…”
Section: Treatment Of Patients Failed By Daasmentioning
confidence: 99%
“…Despite this, levels of HBV DNA and HBeAg clearance for CHM formula granules were much lower than for antivirals [50] or interferon [51]. This is a similar finding for patients with HCV RNA and HCV RNA clearance levels for CHM formula granules were much lower than for antivirals [52].…”
Section: Discussionmentioning
confidence: 74%